Steam Explosion Pretreatment of Lignocellulosic Biomass: A Mini-Review of Theorical and Experimental Approaches - Ziegler-Devin, Isabelle; Chrusciel, Laurent; Brosse, Nicolas (Frontiers in Chemistry, 2021)
Steam Explosion (SE) is one of the most efficient and environmentally friendly processes for the pretreatment of lignocellulosic biomass. It is an important tool for the development of the biorefinery concept to mitigate the recalcitrance of biomass. However, the two distinct steps of SE, steam cracking and explosive decompression, leading to the breakdown of the lignocellulosic matrix have usually been studied in empiric ways and clarifications are needed. This mini-review provides new insights and recommendations regarding the properties of subcritical water, process modeling and the importance of the depressurization rate.